Snow depth measurements collected 2024-04-09 to 2024-04-15 with a magnetic snow depth probe: Kuup Ilua (Blæsedalen) on Qeqertarsuaq (Disko Island), Kalaallit Nunaat (Greenland) - Cable, William L; Bauriedl, Sofia; Mewes, Lars-Hendrik; Stuenzi, Simone Maria; Boike, Julia (In: Boike, Julia; Bornemann, Niko; Cable, William L; Gottuk, Jannika; Hammar, Jennika; Kaiser, Soraya; Kutzbach, Lars; Mewes, Lars-Hendrik; Stuenzi, Simone Maria (2025): Comprehensive snow, soil, water, and climate data from Qeqertarsuaq (Disko Island), West Kalaallit Nunaat (Greenland), 2022-2025 [dataset bundled publication]. PANGAEA, https://doi.pangaea.de/10.1594/PANGAEA.986675 (DOI registration in progress), 2025)
The dataset contains over 1600 snow depth and positional (GNSS) measurements collected along three transects, a moraine and lake in Kuup Ilua (Blæsedalen) on Qeqertarsuaq (Disko Island), Kalaallit Nunaat (Greenland), during a field campaign from April 9 to 15, 2024, as part of the MOMENT project - Permafrost Research Towards Integrated Observation and Modelling of the Methane Budget of Ecosystems. The measurements reach values of up to 243 cm, representing approximately the annual maximum snow depth. The snow depth was measured with an in-house built Magnetic Snow Depth Probe (MagnaProbe). The MagnaProbe measures snow depth along transects or in grids as the observer walks or skis on the snow surface. To make a measurement, the measurement rod is pushed through the snowpack to the ground surface, while a plastic disk on the rod remains on the snow surface. The device then measures the position of the plastic disk on the metal rod, the snow depth. The GPS position is also recorded simultaneously so the result is a dataset with snow depth and position. The position estimates of the GPS were improved using an Emlid GNSS system. The system consisted of an RS2+ operated as a base station and a Reach M+ connected to the MagnaProbe as a rover. In this configuration the MagnaProbe received RTK corrected position information, improving position estimates from 2-3 m (GPS) to cm-level accuracy.
Keywords: Arctic; Disko Island; GNSS; Greenland; Kalaallit Nunaat; Qeqertarsuaq; snow depth